(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Waste from Electrical and Electronic Equipment (WEEE) or Electronic Waste (E-waste) comes under a special category of waste which is the result of industrialization and ever increasing demand of electronic products in our daily life. With increasing usage of these products waste production is also increasing and leads to continuous depletion of finite natural resources and leading us to an uncertain future. Total number of mobile phone subscribers was 116.55 million at June 2014, about 35 % of the active mobile phone subscribers were account for the dual Subscriber Identity Module (SIM) mobile phone set (MPS) and total volume of this is 990 m³, cumulatively the total weight is 1125 ton. Most of the amounts of these mobile phone sets are added per year in the total waste stream of Bangladesh. Only 2-3 % of these amounts of MPSs were recycled through the informal sector and recovered some precious metals also. If we can recycled the entire amount of MPSs about 348.75 kg gold, 105.75 kg of platinum and palladium, more than 163.29 ton of aluminum and 214.32 ton of copper can be recovered. However, these can be the basis of a sustainable material recycle industry to recover materials from the end-of-life mobile phones. J. Environ. Sci. & Natural Resources, 9(1): 91-94 2016